Screw Fixation Versus Hemiarthroplasty for Nondisplaced Femoral Neck Fractures in the Elderly: A Cost-Effectiveness Analysis. Issue 7 (July 2020) - Yong, Taylor M.; Austin, Daniel C.; Molloy, Ilda B.; Kunkel, Samuel T.; Jevsevar, David S.; Gitajn, Ida L.
Abstract : Objective: To evaluate the cost-effectiveness of screw fixation versus hemiarthroplasty for nondisplaced femoral neck fractures in low-demand elderly patients. Methods: We constructed a Markov decision model using a low-demand, 80-year-old patient as the base case. Costs, health-state utilities, mortality rates, and transition probabilities were obtained from published literature. The simulation model was cycled until all patients were deceased to estimate lifetime costs and quality-adjusted life years (QALYs). The primary outcome was the incremental cost-effectiveness ratio with a willingness-to-pay threshold set at $100, 000 per QALY. We performed sensitivity analyses to assess our parameter assumptions. Results: For the base case, hemiarthroplasty was associated with greater quality of life (2.96 QALYs) compared with screw fixation (2.73 QALYs) with lower cost ($23, 467 vs. $25, 356). Cost per QALY for hemiarthroplasty was $7925 compared with $9303 in screw fixation. Hemiarthroplasty provided better outcomes at lower cost, indicating dominance over screw fixation. Conclusions: Hemiarthroplasty is a cost-effective option compared with screw fixation for the treatment of nondisplaced femoral neck fractures in the low-demand elderly. Medical comorbidities and other factors that impact perioperative mortality should also be considered in the treatment decision. Level of Evidence: Economic Level III. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.